Impact of AI on Future Workforce: A Study on Oil & Gas Sector - Salim, Sajam Ebrahim (Digital Repository of Theses, 2025)
Technological advancements in areas such as "Robotic Process Automation" (RPA), "Machine Learning" (ML), and "Artificial Intelligence" (AI) are having a profound impact on the "Oil and Gas" (O&G) industry. This research goals to understand the following questions related to specification of AI effects on O&G sector and workforce components, job position, organizational outlook, and skills disparities in the future. By examining how automation reshapes traditional tasks and creates new opportunities, the research provides insights into workforce planning for “International Oil Companies” (IOCs) and “National Oil Companies” (NOCs). The study uses surveys with structured questions and adapts a quantitative approach collecting data from 300 participants working at IOCs and NOCs across various ranks. A 5-point Likert scale means that perceptions regarding automation and opportunities in employment and reskilling are measured. Quantitative data is analyzed with statistical instruments that help identify patterns and associations about fear of automation, perceived opportunities, and effects of the education level. Research findings show that AI has both positive and negative effects on the consideration of the workforce. As automation takes over more routine and repetitive tasks, raising concerns about job losses, AI also creates new job opportunities in high-tech fields such as data science, AI monitoring, and cybersecurity. The research also points to the fact that organizations require strategies that are robust on reskilling and general working models that will support the responsible use of AI. Therefore, the right balance needs to be made on the use of AI in O&G industry that focuses on the workforce and, at the same time, benefits from the proper advancement of technology. Focused training and education, successful organizational change and learning organization culture are among the primary strategically important factors that unlock a sustainable and efficient labor force. Based on this research, the following findings have been reached: highlighting importance of human resources and leadership to take on the dynamics and possibilities of O&G sector digitalization process.